2018
DOI: 10.31332/lkw.v4i2.852
|View full text |Cite
|
Sign up to set email alerts
|

Constructing WH-Questions Througn An Error Analysis at Junior High School of Indonesia

Abstract: This research aims at finding out the types of errors committed by the students in making wh questions. The researcher applies descriptive research. It is used to describe the errors of the students. in making wh-questions. The population of this research is the second year students of SMP Negeri 2 Bua Ponrang. The total number of population in this research is 240 students. The researcher uses purposive sampling technique in determining class VIII A. Therefore, the total number of sample in this research is 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
1
6
3
Order By: Relevance
“…In P12's, 'are' are should have been placed between business and they. The finding supports the study of Masruddin and Karmila (2018) that revealed that one of the errors committed to constructing wh-questions is misordering. Clearly, misordering errors are caused by incorrect placement of a morpheme or group of morphemes in a given utterance (Tizazu, 2014).…”
Section: Resultssupporting
confidence: 88%
“…In P12's, 'are' are should have been placed between business and they. The finding supports the study of Masruddin and Karmila (2018) that revealed that one of the errors committed to constructing wh-questions is misordering. Clearly, misordering errors are caused by incorrect placement of a morpheme or group of morphemes in a given utterance (Tizazu, 2014).…”
Section: Resultssupporting
confidence: 88%
“…The first error type was "Wrong Wh Question Word," which had the highest number of Saudi students' errors (113 errors out of 300 wh questions). Compared to the previous studies, this finding does not support other studies' findings where the "Wrong Wh Question Word" category received one of the least categories of EFL learners' errors (Iqramah, 2018;Masruddin & Karmila, 2018;Rowland, 2006;Nurjanah et al, 2018;Pathan,2021, Al-Mekhlafi, 2013Addaibani, 2017). Then, "Incorrect Verb Tense" had the second rank in which students made 35 errors.…”
Section: Reasons and Sources Of Participants' Errorscontrasting
confidence: 99%
“…The "Auxiliary Omission" is the sixth category in which there was no auxiliary used in the question, such as the morning movie start; in this case, the participant did not use the auxiliary verb "did" to be as did the movie start this morning? In this study, this category "Auxiliary Omission" ranked sixth, while in all the previous studies globally or locally, it was the first error category of both wh and yes/no questions (Rowland, 2006;Irfaniaah, 2014;Nurjanah et al, 2018;Masruddin & Karmila, 2018;Pathan,2021, Al-Mekhlafi, 2013Addaibani, 2017). It is worth mentioning that this study came up with exciting and surprising results.…”
Section: Redundantcontrasting
confidence: 41%
See 2 more Smart Citations